KREATIVITAS GURU PADA PEMBELAJARAN IPS DALAM MENGGUNAKAN PENDEKATAN SAINTIFIK DI SMP NEGERI 1 TAMBAN KABUPATEN BARITO KUALA - Rahmad Jayadie (Universitas Lambung Mangkurat, 2015)
This certainly brings great effects to teaching and learning process, and one of the effects is the implementation of Scientific Approach which develops 5M (observing, questioning, experimenting, reasoning and communicating). It requires the understanding of the teachers of social studies on teaching and learning in elaborating the scientific approach used in Curriculum 2013. The research method is descriptive qualitative. The primary data sources are two Social Science teachers at SMPN 1 Tamban and the secondary data sources are taken by observation, interview and documentation. The research results showed that Social Science teachers in SMP Negeri 1 Tamban have understood the teaching and learning approach of Curriculum 2013 which is scientific with 5 M activities including observing, questioning, experimenting, reasoning and communicating or collaborative networking. With the facilities and infrastructures which are less supportive toward scientific teaching and learning activities in Social Science, the teachers of SMP Negeri 1 Tamban have been able to develop their creativity by directing students to think critically and creatively to build their independence in solving social problems in society. This can be exposed through the use of scientific teaching and learning model like Problem-Based Learning, Discovery and Inquiry. Social Science teachers creativity in scientific teaching and learning activities can be seen in the teachers efforts in the formulation of the lesson plan based on the steps in the scientific teaching and learning activities, the preparation of materials, the classroom management, media use, the utilization of study sources, the implementation of a teaching and learning model and the submission of study results.Key Words: creativity of teachers, teaching and learning process of social studies, scientific approach